2014
DOI: 10.1016/j.learninstruc.2013.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The paradoxical effect of controlling context on intrinsic motivation in another activity

Abstract: International audienceControlling instructions typically undermine intrinsic motivation. However, in line with an autonomy restoration process, we hypothesized that prior exposure to a controlling context could increase intrinsic motivation displayed in a subsequent task if this second task is devoid of autonomy threats. A correlational study in educational context provided support for this effect by showing that students reported more interest in their music class when it was preceded by a class that was cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 37 publications
4
29
1
4
Order By: Relevance
“…At first glance, findings of this study seem to be in conflict with a line of studies conducted by Radel et al (2013Radel et al ( , 2014. As autonomy is a fundamental psychological need, when faced with autonomy frustration, it is unlikely that individuals would just sit there and do nothing.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…At first glance, findings of this study seem to be in conflict with a line of studies conducted by Radel et al (2013Radel et al ( , 2014. As autonomy is a fundamental psychological need, when faced with autonomy frustration, it is unlikely that individuals would just sit there and do nothing.…”
Section: Discussioncontrasting
confidence: 89%
“…Thus, we played audio instructions incorporating the controlling elements to induce autonomy frustration during Session 1. This approach is in accordance with a few pioneering studies (Reeve et al, 1999;Radel et al, 2014;Weinstein et al, 2017). Specifically, when participants in the experimental group were working on the first task, we played controlling audio instructions incorporating frequent deadlines, specified solutions, orders and requests.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, a single task was adopted in most studies, neglecting the fact that a person may work on multiple tasks in a row, and that one's experience and psychological state in a prior task may have a considerable impact on one's motivation and engagement in a following task (Newton et al, 2020). In recent years, several pioneering studies found that frustration of the fundamental psychological needs would induce a restorative response (Radel et al, 2011(Radel et al, , 2014Fang et al, 2018Fang et al, , 2019. For instance, in an experiment with a two-session between-subject design, Fang et al, 2018 introduced competence frustration to participants in the experimental group and provided the opportunity of competence restoration to participants in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting autonomous motivation has emotional, cognitive, and behavioral consequences for students and their self-regulated learning (Ng et al, 2012;Radel, Pelletier, Baxter, Fournier, & Sarrazin, 2014). Effort regulation and deep-processing of information are two specific aspects of self-regulation (Pintrich, 2004).…”
Section: Motivation: Self-determination Theorymentioning
confidence: 99%